PEMBERIAN KOREKSIAN JAWABAN DISERTAI PENJELASAN UNTUK MEREMEDIASI KESALAHAN SISWA PADA PEMANTULAN CAHAYA DI SMP - F03109036, M.HAMIDI; DJUDIN, TOMO; OKTAVIANTY, ERWINA (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2014)
Abstract: The aim of this research is to determine the effectiveness of providing the feedback in the form of answer sheet correction with teachers explanations to remediate student mistake on reflection of light in SMP Bumi Khatulistiwa Sungai Raya. This research used pre experimental design which was formed in one group pre-test post-test design. Sample of this research was done by random sampling technique with intact group to 20 students in the class IX B. Means of data collecting in essays form consists of 8 questions. The data analysis result showed that providing the feedback in the form of answer sheet correction with teachers explanations effective to remediate student mistake of the average proportion value, the result shown decline from the students who got a mistake as much as 0.41, it was in moderate effectiveness. Providing the feedback in the form of corrected answer along with teacher's explanation can be an alternative to remediate students' mistake in subject material about light reflection. Keyword: Answer Correction, Mistake , Light Reflection Abstrak: Penelitian ini bertujuan untuk mengetahui efektivitas pemberian umpan balik berupa koreksian jawaban disertai penjelasan guru untuk meremediasi kesalahan siswa pada materi pemantulan cahaya di SMP Bumi Khatulistiwa Sungai Raya. Metode penelitian yang digunakan yaitu Pre-Experimental design dengan bentuk one-group pretest posttest design. Pengambilan sampel dilakukan secara random sampling dengan teknik intact group yaitu sebanyak 20 siswa di kelas IX B. Alat pengumpul data berbentuk esai terdiri dari 8 soal. Hasil analisis data menunjukkan pemberian umpan balik berupa koreksian jawaban disertai penjelasan guru efektif untuk meremediasi kesalahan siswa dengan harga rata-rata proporsi penurunan siswa yang mengalami kesalahan sebesar 0,41 tergolong sedang. Pemberian umpan balik berupa koreksian jawaban disertai penjelasan guru dapat dijadikan alternatif dalam meremediasi kesalahan siswa pada materi pemantulan cahaya.